Testicular histopathology as a predictor of a positive sperm retrieval in men with non‐obstructive azoospermia. (15th May 2012) - Abdel Raheem, Amr; Garaffa, Giulio; Rushwan, Nagla; De Luca, Francesco; Zacharakis, Evangelos; Abdel Raheem, Tarek; Freeman, Alex; Serhal, Paul; Harper, Joyce C.; Ralph, David
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? The management of patients with non‐obstructive azoospermia (NOA) involves testicular sperm extraction (TESE or microdissection TESE) combined with intracytoplasmic sperm injection (ICSI). Sperm retrieval is successful in up to 50% of men with NOA; however, there is no single clinical finding or investigation that can accurately predict a positive outcome. Several studies have concluded that testicular biopsy is the best predictor of a successful TESE. The present study shows that the strongest predictor of the success of TESE is when tubules with mature spermatozoa (Johnsen score ≥8) are found in the histopathology specimen, irrespective of the overall state of spermatogenesis. The findings suggest that a lower limit threshold value of 2% of tubules with spermatogenesis in the histopathology specimen will result in a positive sperm retrieval. However, it is not practical to perform a diagnostic biopsy before TESE because this would mean that patients undergo two surgeries, which adds to the cost and increases the complications. The diagnostic biopsy is best coupled with an initial TESE before starting the ICSI cycle. Based on the findings of the histopathology specimen, patients may be then offered a repeat TESE if more sperm is needed on the day of ovum pick‐up and ICSI. Also, if the initial TESE was negative, the biopsy result will help in the decision to offer a repeat TESE. This regimen is more cost‐effective because the ICSI cycle will be started only if adequate sperm is retrieved. Objective To assess whether testicular histopathology can predict the outcome of testicular sperm extraction (TESE) in men with non‐obstructive azoospermia (NOA) and therefore the role of preoperative diagnostic testis biopsy. Patients and Methods The study comprised a retrospective analysis of 388 patients with azoospermia who were referred from 2005 to 2010. Information collected included a clinical history and an examination including age and testicular size, serum follicle‐stimulating hormone, two semen analyses and testicular histology collected at the time of surgical sperm retrieval (TESE or microdissection TESE). Results In total, 388 patients with a mean (range) age of 37 (18–66) years were included in the present study. Based on the history, clinical and laboratory findings, 112 patients had obstructive azoospermia and 276 patients had NOA. All patients in the obstructed group had a positive sperm retrieval. The sperm retrieval rate for the NOA group was 50%. An analysis of the results showed that the best predictor of a positive sperm retrieval was when tubules with mature spermatozoa were seen at biopsy, irrespective of the overall state of spermatogenesis (P < 0.001). Conclusions The presence of tubules with spermatazoa on biospy is the best predictor of a positive surgical sperm retrieval in patients with NOA. The diagnostic biopsy is best coupled with an initial TESE before starting the intracytoplasmic sperm injection (ICSI) cycle. Based on the findings of the histopathology specimen, patients may be offered a repeat TESE if more sperm is needed on the day of ovum pick‐up and ICSI, or a redo TESE if the initial TESE was negative.